Mineralogical stabilization and morphology of hardystonite Petedunnite-Dicalcium silicate ternary mixtures. (2022) - Agourrame, H.; Moudar, J.; Khachani, N.; Taibi, M.; Diouri, A.
Highlights: The characterization of the developed phases indicates the formation of mixtures of C2 S with Hardystonite Ca2ZnSi2O7 phase of the tetragonal crystal system and Petedunnite phase (CaZnSi2O6) of the monoclinic crystal system. Zinc is incorporated easily into the C2S phase as a substituting element for calcium and stabilize both the allotropic varieties α and β, increasing the percentage of Zinc nitrates changes the C2S polymorph from β to α. The incorporation of zinc from nitrate gives morphology of fine porous particles in the form of hexagonal platelets. Abstract: Zinc metal, charge carrier, incorporated into silicate phases can give them properties for specific applications; it appears a promising field to solve several problems associated with the use of this type of silicate materials. The aim of this study is to incorporate Zn from Zinc nitrate (Zn (NO3 )2 ) into dicalcium silicate to produce novel cement containing hardystonite phase (Ca2 ZnSi2 O7 ) and Petedunnite phase (CaZnSi2 O6 ). These phases were synthesized by solid state reaction. Samples were prepared by the addition of different proportions of 0%, 1%, 2%, 3% 5% of the nitrates of Zn to the reactants CaCO3 and SiO2 of ratio Ca/Si = 2, the synthesis was carried out by heating the finely ground mixtures at temperatures ranging from 500 to 1000 °C. XRD, FTIR and SEM were performed on the samples to characterize the mineralogical and microstructure proprieties. According to XRD results, the characterization of the developed phases indicates the formation of mixtures of C2 S with Hardystonite Ca2 ZnSi2 O7 phase of the tetragonal crystal system and Petedunnite phase (CaZnSi2 O6 ) of the monoclinic crystal system. The micrographs obtained by SEM and EDS analysis show that the addition of zinc from nitrate gives morphology of fine porous particles in the form of hexagonal platelets.